Pengembangan Media Pembelajaran Permainan Kartu Uno Pada Mata Pelajaran IPA Materi Ekosistem - Devi Agustriyani; Nana Hendracipta; A. Syachruroji (Jurnal Lensa Pendas, 2024)
This development research aims to develop a product in the form of Uno cards as a learning medium that contains science lessons on ecosystem themes with feasibility tests and student responses. The research method uses the Research and Development (R&D) method with 3D design including Definition, Design and Development. The research instrument is a questionnaire with a Likert scale for feasibility testing by a team of experts and a student response questionnaire. The results of the feasibility test for the Uno card learning media by a team of material experts were assessed as very feasible reaching 85%, media experts assessed it as very feasible reaching 85% and language experts assessed it as very feasible reaching 88%. The average result of all validators is 86% in the very feasible category. Product trials were carried out on grade 5 students at SD Negeri Merak III in the even semester of the 2023/2024 academic year. The results of the student response test reached the very good category of 85%. Based on the results of expert validation and limited trials on students, the Ukos card game media can be a learning media that is suitabel for use in the learning process in schools.